Not born digital : poetics, print literacy, new media - Morris, Daniel, 1962- (New York : Bloomsbury Academic, 2016)
'Not Born Digital addresses from multiple perspectives - ethical, historical, psychological, conceptual, aesthetic - the vexing problems and sublime potential of disseminating lyrics, the ancient form of transmission and preservation of the human voice, in an environment in which e-poetry and digitalized poetics pose a crisis (understood as opportunity and threat) to traditional page poetry. The premise of Not Born Digital is that the innovative contemporary poets studied in this book engage obscure and discarded, but nonetheless historically resonant materials to unsettle what Charles Bernstein, a leading innovative contemporary U.S. poet and critic of'official verse culture,' refers to as'frame lock' and'tone jam.' While other scholars have begun to analyze poetry that appears in new media contexts, Not Born Digital concerns the ambivalent ways page poets (rather than electronica based poets) have grappled with'screen memory' (that is, electronic and new media sources) through the re-purposing of'found' materials'--
'Breaks new ground by evoking framework models of art theory to approach innovative U.S. poetry, with special emphasis on 21st-century examples of conceptual authors whose'found' material first appeared in new media contexts'--
Machine generated contents note: -- 1. This is Just to Say This is the End of Art: Williams and the Aesthetic Attitude -- 2. Medium as Messenger as Medium as Messenger: Hannah Weiner Anchor's the Social Poetics of 1986 in Weeks -- 3. Bibliodeath: What is an Archive in a Digital Era? -- 4. Gaps in the Machine: On Andrei Codrescu's Unarchival Poetics -- 5.'Tech support says'Dead Don Walking': Tradition, the Internet, and the Individual Talent in the Poetry of Daniel Y. Harris -- 6. (In)decisive Moments: On Kenneth Goldsmith's Seven American Deaths and Disasters -- 7. On Soliloquy: Kenneth Goldsmith as Conceptualist at the cusp of a Digital Age -- 8. Bad Company, Meet Sonic Youth: On Noah Eli Gordon's Inbox -- 9.'Cum on Feel the Noize': The Erotics of Literary Activism in an Age of Internet Viruses in An Army of Lovers -- 10. Ai Wei Wei's Dirty ConceptualismBibliography -- Index.
Bibibliography : page [239]-250.
Keywords: American poetry -- 21st century -- History and criticism -- Theory, etc; Experimental poetry, American -- History and criticism; Poetics -- History -- 21st century; Avant-garde (Aesthetics) -- United States -- History -- 21st century; Art and literature -- United States